Reducing hot cracking tendency of dissimilar weld overlay by magnetic arc oscillation. (August 2014) - Yu, X.; Lim, Y. C.; Smith, R.; Babu, S. S.; Farson, D. F.; Lippold, J. C.; McCracken, S.
<x content-type="archive" xml:space="preserve">Abstract</x> Nickel filler metals are used for joining and repair of dissimilar metal welds in nuclear power plants. However, with some compositions of austenitic stainless steel base metals, weld cracking is observed. In the present work, the solidification cracking behaviour of 52M overlay on stainless steel with and without magnetic stirring was studied. Single, double and triple bead on plate experiments with 52M filler wire were performed on a type 303 stainless steel plate cladding with a single layer of ER308LSi stainless steel. Weldings were then performed with and without magnetic stirring. Although cracking tendency was observed in all experiments, it was seen that magnetic stirring significantly reduced the cracking tendency. Confirmatory electron backscattered diffraction analyses confirmed the grain refinement in 52M beads with magnetic stirring.